Saving Industry of Garments Solid Works In West Java (Review of SE and SK Determination Policy on West Java UMK in 2020) - Muhamad Rizal; Anang Muftiadi (Jurnal Manajemen Pelayanan Publik, 2020)
It has become a common tradition that in November every year, each Governor is obliged to set a UMP and can (not must) determine Regental/Municipal Minimum Wage (UMK). This is regulated by PP 78 of 2015 concerning Wages. This wage policy regulates the minimum wage that must be paid by employers to all workers without exception. Every year, this wage arrangement has become a problem for the industry, especially labor-intensive industries. This industry contributed to employment for people who had only low education around the company and its supporting areas. However, wages that were getting higher each year caused companies to enter the non-compliment category of buyers. This choice was what caused many companies to relocate or permanently disband their companies. Deferral of payment was not a solution for the company. In fact, it dragged them to bankruptcy. Governor of West Java’s SE No. 561/75/Yanbangsos/2019 concerning the Implementation of MSEs in West Java had become a breath of fresh air for the investment climate in West Java. However, this SE did not last long because of the high pressure of interest on the Governor of West Java. This article was carried out to analyze the impact of the revocation of the SE and the change to a decree, which stagnated the industry and reduced its production resulting in massive layoffs in several Regencies and Cities in West Java.